Are Three Better than Two? – : Incidental Finding of Incomplete Cor Triatrium Dextrum during 2nd Trimester of Pregnancy - Holtzapple, Zachary (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.